2013
DOI: 10.5539/ijbm.v8n22p1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Human Resource Management Practices, Organisational Culture, Organisational Innovation and Knowledge Management on Organisational Performance in Large Saudi Organisations: Structural Equation Modeling With Conceptual Framework

Abstract: The conceptes of human resource management practices, organisational culture, knowledge management, organisational innovation, and organisational performance in the human resource management research field have been implemented. Although the results of literature were significant, no studies were released in order to conduct a study about the function of human resource management practices in intensifying the organisational performance with interfering organisational culture, knowledge management, and organisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 80 publications
(57 reference statements)
5
42
0
1
Order By: Relevance
“…Another external factor found to have a positive relationship with knowledge sharing attitude is rewards. Our finding concurred with several Middle Eastern studies (e.g., Al-Bahussin and El-Garaihy, 2013;Al-Alawai et al, 2007;Migdadi, 2009) where incentives were found to drive knowledge sharing to achieve practical results. Although tangible incentives are crucial for promoting the desired behaviour, our study found that indirect rewards such as opportunities to assume leadership roles, exposure to different areas of work and a longer-term recognition in terms performance are better able to sustain the right attitude towards knowledge sharing (c.f., Liu and Liu, 2011).…”
Section: Factors Affecting Knowledge Sharing Attitudesupporting
confidence: 82%
See 2 more Smart Citations
“…Another external factor found to have a positive relationship with knowledge sharing attitude is rewards. Our finding concurred with several Middle Eastern studies (e.g., Al-Bahussin and El-Garaihy, 2013;Al-Alawai et al, 2007;Migdadi, 2009) where incentives were found to drive knowledge sharing to achieve practical results. Although tangible incentives are crucial for promoting the desired behaviour, our study found that indirect rewards such as opportunities to assume leadership roles, exposure to different areas of work and a longer-term recognition in terms performance are better able to sustain the right attitude towards knowledge sharing (c.f., Liu and Liu, 2011).…”
Section: Factors Affecting Knowledge Sharing Attitudesupporting
confidence: 82%
“…A key internal factor affecting knowledge sharing attitude is openness which has been found to develop trust between knowledge users and collaborators (e.g., Al-Bahussin and El-Garaihy, 2013;Argote and Ingram, 2000;Lane and Bachmann, 1998). However, our study found that both openness and trust contribute differently to knowledge sharing attitude.…”
Section: Factors Affecting Knowledge Sharing Attitudementioning
confidence: 99%
See 1 more Smart Citation
“…As such, training is growing to be more common although the subject is progressive in the academic arena. Training effectiveness is a very wide research area that can be researched from various angles (Al-Bahussin & Elgaraihy, 2013). Effective training connects properly all the parties involved in the business those are organizations, employees, and customers by the practice of transferring knowledge gained by the employee from training in the work environment; therefore, it serves the organization's competitiveness ability including public sector organizations (Chen, Yang, & Chen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In regard to the evolution of the role of human resource, it was mainly the subjective points of view, the judgment, and the perception of human resource managers that were mostly reflected in the research on the changes of the role of human resource, while human resource practitioners presented limited effects. Al-bahussin and El-garaihy (2013) further indicated that the role of human resource could not give up the past myth, and the human resource strategic image created for the future was far beyond the achievability so that the role of human resource might return to the past fuzziness in facing old roles, but simultaneously face the uncertainty of future roles.…”
Section: Research Background and Motivationmentioning
confidence: 99%